Approaches to the treatment of bullous pemphigoid (Research, Society and Development, 2022)
Bullous pemphigoid is a rare disease evidenced by a generalized vesiculobullous eruption that most commonly affects the elderly and children. Given the above, the study aims to analyze the treatments for bullous pemphigoid. This is an integrative literature review carried out using the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. of the following Descriptors in Health Sciences (DeCS): "bullous pemphigoid" and "therapeutic". Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme , in the last ten years (2012-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. 57 articles were found, after the combined search of descriptors and Boolean operators, 5 articles were selected to compose the final sample.Therapeutic should be chosen based on the degree of disease, type of disease, patient age group and associated comorbidities.